PENINGKATAN PRODUKSI PADI, PENDAPATAN DAN EFISIENSI PENGGUNAAN SUMBERDAYA MELALUI PENERAPAN SISTEM TANAM JAJAR LEGOWO PADA MINAPADI - Sumarsih, Enok; Natawidjaja, Ronnie S.; Silmi, Ajeng (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2020)
The research objective was to analyze the increase of rice production, income, and resource efficiency (land, labor, and capital use) of minapadi applicating ?jajar legowo? plant spacing, a case in Sirnasari Village, Sariwangi Sub-District, Tasikmalaya Regency. The survey method was used in the research. 35 minapadi farmers applicating the jajar legowo plant spacing and 8 minapadi farmers implementing the tegel plant spacing were taken as samples from a population size of 78 farmers. Comparative descriptive analysis was used to determine differences in production, income and resources efficiency (the use of land, labor, and capital). Unpaired t-test was used to test differences in rice production and farmers? income applicating the jajar legowo and tegel plant spacing. The results showed that minapadi applicating the jajar legowo plant spacing increased rice production, fish production, and farmers' income by 18.25, 32, and 40 percent respectively. The resources use of land, labor, and capital in minapadi applicating the jajar legowo plant spacing was more efficient than that of applicating the tegel plant spacing.